Financial Feasibility Analysis of Constructed Wetland Phytoremediation WWTP (Case Study: Faculty of Agricultural Technology, XYZ University) - Elida Novita; Resta Dwi Ismaniar Rahmadaningtyas (Jurnal Rekayasa Lingkungan dan Biosistem, 2023)
Laboratory activities at the Faculty of Agricultural Technology, University of XYZ produce wastewater that is still dumped directly into the environment. Wastewater content such as pH, TDS, TSS, BOD and COD that exceed quality standards cause potential damage to the environment, especially the river environment. The construction of the constructed wetland phytoremediation wastewater treatment plant aims to manage laboratory wastewater to be safe when it is made into the environment. The purpose of this study is to calculate the value of financial feasibility and cost-benefit value of wetland phytoremediation wastewater treatment plant. The results of the calculation of the value of financial analysis by the method of analysis NPV, IRR, BCR, PBP, shows the NPV value of Rp. 7.456.063; IRR value of 12%; BCR value of 1,06%, and PBP value for 1 year so that the wastewater treatment plant construction project feasible. The value of benefits to costs has a value of 1,05 means the project is feasible because the value of the benefits provided is greater than the costs used.